Problem Tree Analysis of Plastic Waste Accumulation on The Tuban Coast and Decision Making Using the Rational Model - Arya Pratama Sagita Putri (Universitas Negeri Gorontalo, 2026)
The coastal areas of Tuban Regency are facing an urgent ecological pollution crisis due to the massive accumulation of plastic waste, which has led to a decline in environmental quality and high levels of microplastic contamination in the waters. This study aims to identify and formulate the most appropriate and optimal public decision-making steps to resolve the plastic waste problem in the coastal areas of Tuban. The method used is a descriptive qualitative approach based on a literature review. The analytical framework integrates Problem Tree Analysis to logically diagnose the root causes of the problem (such as the lack of Integrated Waste Processing Facilities and community waste disposal behavior), as well as the Rational Model to formulate, evaluate, and determine the best solution from various available alternatives. The results of the analysis indicate that the most effective and comprehensive solution is to combine the establishment of Integrated Waste Processing Facilities (IWPFs) with the adoption of RECYFUEL pyrolysis technology. This applied technology has been proven capable of thermally decomposing waste, converting 1 kg of marine plastic waste into 300–400 ml of diesel-equivalent alternative fuel. The conclusion of this study indicates that the implementation of public policies integrating RECYFUEL infrastructure and technology is not only effective in reducing the volume of plastic pollutants along the coast but also capable of creating self-sustaining economic empowerment for local communities, which aligns with the achievement of the Sustainable Development Goals (SDGs).